MUHAMMAD ALI PASHA: INOVASI PENDIDIKAN ISLAM - Harahap, Radinal Mukhtar (Idrak: Journal of Islamic Education, 2018)
History, although in basic understanding seems to talk about something that has passed, actually save a lot of lessons. This paper departs from a character's study of Muhammad Ali Pasha who made many innovations in the field of Islamic education. He was found as a person who has a unique side, namely his personality who has no history of education in childhood because of the pressure of life but grew as a leader who made many innovations. Some innovations that can be called are its policy of putting the government as the center that develops education itself. Another innovation is the ongoing traditional and modern educational activities together so that the scientific scope is separated from the dichotomous aspects. Muhammad Ali Pasha was also noted as a leader who paid attention to the development and expansion of the education area so as to bring in European teachers to be able to take their expertise and practice in the Egyptian region, besides sending Egyptian youth to study in other regions to become cadres in the realm he wanted to grow and develop. Even so, it does not mean that Muhammad Ali Pasha's contribution and contribution in educational innovation can be swallowed up to be realized in Islamic educational institutions. More in-depth assessment of aspects, content and impacts that have been carried out to take what is needed and leave what is not needed.